Makna kata Khalifah Dalam Qs. Al-Baqarah [2] : 30 ( Studi Komparasi Tafsir Al Manar Dan Jawahir) - Syahla Ghaziyah Salsabil; Imansyah Imansyah; Hanief Monady (JOURNAL SAINS STUDENT RESEARCH, 2025)
Humans, as khalifah (stewards) on Earth, have a great responsibility to lead and manage all aspects of life, whether in the family, society, or state, which will be accountable in the hereafter. This study examines the meaning of "leader" in QS. Al-Baqarah verse 30 through a comparative tafsir study between Al-Manar (Syekh Rasyid Ridha) and Al-Jawahir (Syekh Tantawi Jauhari), using Max Weber’s charismatic leadership theory. The research method employed is qualitative with a hermeneutic approach, utilizing primary data from the Qur'an and tafsir, and secondary data from books, articles, and journals. The findings show that leaders in Islam have a trust (amanah) to preserve the Earth and manage natural resources wisely. A just, trustworthy, and wise leader will safeguard the welfare of the community and the Earth. This study concludes that a leader should lead with integrity, be accountable for their actions, and prioritize the common good and environmental sustainability.